Comparing students’ thermochemistry misconceptions after the PDCA metacognitive learning and the 5E learning cycle: A subtopic-based diagnostic study - Sofinila, Mida Fitri Agasty; Parlan, Parlan; Muntholib, Muntholib (Indonesian Journal of Science and Mathematics Education, 2026)
Students’ misconceptions in thermochemistry remain challenging, as the topic requires integrated conceptual, representational, and mathematical understanding. Although many studies have examined thermochemistry misconceptions, limited attention has been given to subtopic-based comparisons after learning through strategies with different characteristics. This study compares students’ misconception patterns across thermochemistry subtopics after implementing the PDCA metacognitive learning strategy (SM-PDCA) and the 5E Learning Cycle (LC 5E) using four-tier diagnostic evidence. A comparative descriptive quantitative design involved 65 eleventh-grade students from two intact classes at SMAN 5 Malang. Misconceptions were diagnosed using a four-tier test and analyzed by subtopic, answer-reason pattern, and Cohen’s d. The SM-PDCA class showed a lower overall misconception percentage than the LC 5E class (29.22% vs. 33.23%), with the clearest tendency in the system and surroundings and the types of standard enthalpy changes. In contrast, the LC 5E class showed only a slight tendency toward lower misconceptions in determining enthalpy change (ΔH), with a negligible effect size. These findings suggest that the SM-PDCA is particularly relevant to thermochemistry concepts that require monitoring conceptual boundaries, evaluating classifications, and revising reasoning. Chemistry teachers should align instruction with the cognitive demands of each subtopic by combining metacognitive monitoring, structured problem-solving, and explicit conceptual justification.